FOREIGN EXPERIENCE IN PROTECTING THE RIGHTS AND INTERESTS OF MINOR CHILDREN AS A RESULT OF SEPARATION FROM MARRIAGE - M. S. Usmonova (American Journals Publishing, 2025)
It is noteworthy that in recent years a number of research works related to the resolution of family disputes have been carried out in our country within the framework of the discipline of family law. The article analyzes foreign experience in the protection of the rights and interests of minors as a result of separation and the system of national legislation. In particular, issues of supply, mutual and joint obligations of parents to raising children are covered on the basis of foreign experience.
Keywords: Family, family law, agreement, civil relationship, alimony, supply, obligation, law.